Cross-linking in an artificial human cornea via induction of tissue transglutaminases - Kopsachilis, N.; Tsinopoulos, I.; Tsaousis, Konstantinos; Meiller, R.; Dimitrakos, S. A.; Kruse, Friedrich; Luessen, U. W. (Ophthalmologe, 2012)
In recent years many three-dimensional cornea models have been developed. However, they show poor collagen stability in the stroma. Transglutaminases (Tgases) are calcium-dependent proteins which play an important role in cross-linking of the corneal stroma. The purpose of this study was to find out whether it is possible to induce in vitro cross-linking of the stroma in an artificial hemicornea model with the help of Tgases.For the construction of the hemicornea, human SV40 adenovector corneal epithelial cells (HCE) and human SV40 adenovector corneal keratocytes (HCK) were cultivated. Confluent HCK cells were treated for 24 h with transforming growth factor beta (TGFb) 1, 2 and 3 at different concentrations as well as with other growth factors and the treated cells were compared to untreated cultivated cells. The quantification of the expression of the Tgases by HCKs was examined with the use of real time PCR, Western blot imaging and immunochemistry.All concentrations of TGFbs used resulted in a significant increase of Tgase-mRNA, Tgase protein level and Tgase activity. The Tgases remained unaffected after treatment with other growth factors in comparison to untreated control cells. Treatment of the hemicornea with TGFb2 showed a very strong contraction and haze in comparison to the untreated hemicornea.It has been shown for the first time that TGFb induces a strong expression of Tgases in HCK cells. This effect caused an undesired contraction and haze of the human hemicornea model. Further research is necessary in order to find out whether the induction of Tgases in the HCK cells can be regulated without losing stability of the constructed hemicornea.
EVALuna2:21093